Diastolic dysfunction measured by cardiac magnetic resonance imaging in women with signs and symptoms of ischemia but no obstructive coronary artery disease. (1st October 2016) - Wei, Janet; Mehta, Puja K.; Shufelt, Chrisandra; Yang, YuChing; Gill, Edward; Kahlon, Ravi; Cook-Wiens, Galen; Minissian, Margo; Kar, Saibal; Thomson, Louise; Berman, Daniel; Merz, C. Noel Bairey
Abstract: Background: Women with chest pain and no obstructive coronary artery disease often have coronary microvascular dysfunction (CMD), diagnosed by invasive coronary reactivity testing (CRT). The relationship between CMD and diastolic function measured by cardiac magnetic resonance imaging (CMR) is not well described. Methods: 41 women with suspected CMD underwent CRT and CMR. Left ventricular end-diastolic pressure (LVEDP), coronary flow reserve (CFR) and coronary blood flow (CBF) were measured invasively. Resting CMR of these women and 20 reference controls was assessed for LV mass, septal wall thickness, ejection fraction (LVEF), end-diastolic volume (EDV), peak filling rate (PFR) and time-to-peak-filling rate (tPFR). Pearson correlations and linear regression models were made. Results: Mean age was 55 ± 9, all had LVEF ≥ 50%, and 16/41 (40%) had LVEDP > 15 mm Hg. CMD (CFR < 2.5 or CBF < 50%) was present in 34/41 (83%) women. tPFR (mean 178 ± 110 ms) and PFR (mean 3.2 ± 0.64 EDV/s) were not significantly different in women with or without CMD. tPFR increased with age ( r = 0.37, p = 0.017) and septal wall thickness ( r = 0.47, p = 0.002), while PFR decreased with age ( r = − 0.45, p = 0.003). There was an inverse relationship between CFR and tPFR ( r = − 0.3, p = 0.058). Increasing mass was associated with decreasing CBF ( p = 0.02). Compared to controls, cases had lower LVEF ( p = 0.049) and lower EDV ( p = 0.0002). Conclusion: In women with signs and symptoms of ischemia but no obstructive coronary artery disease, CMD and elevated LVEDP are prevalent. While non-endothelial dependent CMD may be related to diastolic dysfunction, further investigation is needed regarding links between CMD, diastolic dysfunction and the development of heart failure with preserved LVEF.